45.9k views
0 votes
(2x+5)(x+1) if anyone knows the answer to it can you please help.

2 Answers

6 votes
(2x-5)(x+1)=2

Move all terms to the left side of the equation and simplify.
2x2−3x−7=0

Use the quadratic formula to find the solutions.
−b±√b2−4(ac)2a

Substitute the values a=2
, b=−3, and c=−7 into the quadratic formula and solve for x
3±√(−3)2−4⋅(2⋅−7)2⋅2

Simplify.
x=3±√654

The result can be shown in both exact and approximate form.
x=3±√654
x≈2.76556443,−1.26556443
User PanCrit
by
5.3k points
5 votes

2x^2+7x+5 you must multiply both equations by each other in the parenthesis

User Riaj Ferdous
by
5.5k points